Estimation of morphology and function of the eye in Usher’s syndrom - Mrugacz, Małgorzata; Szumiński, Michał; Średzińska-Kita, Dorota; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Retinitis pigmentosa (RP) is a set of heterogenous retinal diseases that affect primarily photoreceptors and retinal pigmented epithelium. The Usher’s syndrome (RP associated with hearing impairment or loss), is responsible for about 10-20% of all cases. We investigate macular morphology using spectral domain optical coherence tomography in correlation with visual function. Material and methods: Two patients with Usher syndrome: a 13 years old girl and her 9 years old sister underwent comprehensive ophthalmological examination including: BCVA testing (Snellen charts), biomicroscopy of the anterior and posterior segment of the eye, electroretinography and SD-OCT scans of the macular region. Results: BCVA was noticeable decreased in both eyes (Vod = 5/16, Vos = 5/16), of 13 years old patient, while it was slightly diminished in her younger sister (Vod = 5/6, Vos = 5/6). In patient with visual deterioration a blue cone deficiency was found. Central foveal thickness (CFT) and foveal outer segment/pigment epithelium thickness (FOSPET) was significantly reduced in 13 years old patient. Conclusions: Spectral optical coherence tomography is a useful method to monitor morphological changes of the macula and their progress in patients with retinitis pigmentosa in Usher’s syndrome.